If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(a + 6.2) = 102 Reorder the terms: 10(6.2 + a) = 102 (6.2 * 10 + a * 10) = 102 (62 + 10a) = 102 Solving 62 + 10a = 102 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-62' to each side of the equation. 62 + -62 + 10a = 102 + -62 Combine like terms: 62 + -62 = 0 0 + 10a = 102 + -62 10a = 102 + -62 Combine like terms: 102 + -62 = 40 10a = 40 Divide each side by '10'. a = 4 Simplifying a = 4
| 4C-10=6 | | 3a+(-4)=-2 | | 8-x=1 | | 5x-2(x-3)=-6+5x+8 | | ln(7x+3)=ln(2x-17) | | -3=c-b | | x+3x+4x=365 | | C=4.5N+8 | | 6v+8+3=-17 | | 4=-16+6x | | -2(x-1)=15 | | 1.02x-2y=-18.8 | | 2(-8t^2+7t+1)=0 | | -8(a+2)=-10 | | 20y+2=10 | | 3w+7x-10+2y=8w-9x-16 | | -7x+2=-19 | | -5-(15y-1)=2(7y-16-y) | | 5y-13=6(y+3) | | 5p+5=4p+14 | | 2y(2y+3)=6y(y-1) | | 18*(25*10)=330x | | 125=-5p-5(3+6p) | | 18*(25*10)=330 | | 8z=3x+5x | | -2(x-7)=4(x-2) | | ax-4=9 | | 4+7x-12=4x+12-x | | (q-8)=7q+5 | | -2x-12+3=3+x | | x*x+4y=(x+6)(x-2) | | 3x+3=-2(x-5) |